Предмет: Алгебра,
автор: MashaAmericaLive
Упростите выражение:
(3х^2+2х-1)/(х+1)
Ответы
Автор ответа:
2
(x^2+2x^2+2x-1)/(x+1)
(2x(x+1)+(x+1)(x-1))/(x+1)
((x+1)(3x-1))/(x+1)
3x+1
(2x(x+1)+(x+1)(x-1))/(x+1)
((x+1)(3x-1))/(x+1)
3x+1
Автор ответа:
2
3x²+2x-1=3x²+3x-x-1= 3x(x+1)-(x+1)= (x+1)(3x-1)
(x+1)(3x-1)/(x+1)= 3x-1
Ucus1359:
я так же сделал
Похожие вопросы
Предмет: Биология,
автор: timurshvede5503
Предмет: Русский язык,
автор: Katyaratmanska6778
Предмет: Астрономия,
автор: Alinushcka4050
Предмет: Химия,
автор: Агаран
Предмет: История,
автор: Севуля20060411